Dual therapy of vildagliptin and telmisartan on diabetic nephropathy in experimentally induced type 2 diabetes mellitus rats. (December 2014) - Sharma, Ashish Kumar; Kanawat, Devendra Singh; Mishra, Akanksha; Dhakad, Prashant Kumar; Sharma, Prashant; Srivastava, Varnika; Joshi, Sneha; Joshi, Megha; Raikwar, Sachin Kumar; Kurmi, Muneem Kumar; Srinivasan, Bharthu Parthsarthi
Introduction: The objective of this article is to investigate the combination of telmisartan with vildagliptin therapy versus monotherapy of vildagliptin and telmisartan on diabetic nephropathy in type 2 diabetes mellitus rats. Materials and methods: In adult rats streptozotocin (65 mg/kg) and nicotinamide (110 mg/kg) were injected intraperitoneally to produce diabetic nephropathy. Rats of either sex allotted to the following groups: (i) triple therapy: metformin (120 mg/kg, o.d.) + pioglitazone (1.25 mg/kg, o.d.) + glimepiride (0.7 mg/kg, o.d.); (ii) dual therapy: vildagliptin (8.76 mg/kg, o.d.) + telmisartan (6.48 mg/kg, o.d.); (iii) vildagliptin (8.76 mg/kg, o.d.); and (iv) telmisartan (6.48 mg/kg, o.d.); therapy was carried out for 35 days orally. Weekly at days 7, 14, 21, 28 and 35, blood pressure, blood glucose level, body weight, blood serum creatinine level, protein albumin level in urine, and blood urea nitrogen (BUN) were estimated. Renal structural changes were observed. Results: Blood pressure, blood glucose level, blood serum creatinine level, protein albumin level in urine, BUN and renal deterioration increased significantly in diabetic rats compared with normal control rats. The vildagliptin + telmisartan treatment group showed no weight gain and controlled blood pressure, renovascular structural and biochemical parameters in diabetic neuropathy rats. Conclusions: The addition of telmisartan to vildagliptin demonstrated the best control over blood pressure, glycemia and diabetic nephropathy markers, renal structural changes and improvement of renal function as opposed to monotherapy with either drug, possibly because of the dual inhibitory effect on the renin–angiotensin system.